Travel in the late antique Levant: a study of networks of communication and travel infrastructure in the 4th-7th centuries - Whiting, M (2013)
The purpose of this thesis is to study the travel infrastructure that existed in the Late Antique Levant (defined as extending from southern Asia Minor to the Sinai Peninsula), and how it enabled people to travel around the region for a variety of official, professional or personal reasons. What were the motivations, and what mechanisms facilitated or constrained travel for different groups of people? Road conditions and road maintenance are discussed, as is the availability of amenities, and the means of transport (wheeled vehicles, animals) and the various hazards that travellers might have faced. Chapter 3 addresses the conception of space and distance. This includes not only how geographical space was described, but also how distance was measured and broken up into manageable increments for travel. This chapter details how the incremental landscape was applied, e.g., through the staging posts of the cursus publicus and set itineraries for pilgrimage. Chapter 4 focuses on travel by water, examining the different factors, such as ship construction, seasonal weather patterns, navigation and hazards, to determine whether the risks and benefits were in balance. An examination of the Tigris, Euphrates, and Orontes and their role in transportation relies on a combination of texts and archaeology from Late Antiquity itself, and ethnographic comparanda from both earlier and later periods. Chapter 5 is devoted to specific evidence for networks in the Late Antique Levant. The four case studies look at the connections between the Levant and the imperial capital, military routes to the Mesopotamian frontier, caravan routes through Syria, and pilgrim roads leading to Jerusalem. These strands are brought together in Chapter 6, a regional study of southern Palestine and Transjordan. Changes in routes over time reflect military and commercial concerns, as well as the interest of pilgrims in the holy sites of the area.